High Mobility MoS2 Transistor with Low Schottky Barrier Contact by Using Atomic Thick h-BN as a Tunneling Layer - Wang, Jingli (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.